Peningkatan Keaktifan dan Hasil Belajar Pendidikan Agama Kristen Melalui Model Window Shopping Pada Siswa Kelas IX SMPN 3 Dusun Selatan Kabupaten Barito Selatan - Gloria, Gloria (Harati: Jurnal Pendidikan Kristen, 2022)
The purpose of this study is to improve the liveliness and learning outcomes of students of class IX SMPN 3 South Hamlet in Christian Education through window shopping model. This type of research is Class Action Research. The objects of action studied include the level of activeness of students during teaching and learning activities and student learning outcomes after the completion of each cycle. The subjects of class IX SMPN 3 South Hamlets consisted of 25 people, consisting of 12 men and 13 women. The implementation of research in the 1st semester of the 2021/2022 school year, namely in September to November 2021. The results of this study showed a significant improvement both in the activeness of students and in the value of learning outcomes. The increase in student activity is indicated by an increase in the number of students who are active in the learning process in each cycle. The increase in student learning outcomes is evidenced by an increase in the number of students who can get grades more than or equal to 70 or can reach KKM, namely 20 (80%) students in cycle I increased to 24 (96%) students in cycle II. Thus the student's learning outcomes achieve classical completion. Tujuan penelitian ini untuk meningkatkan keaktifan dan hasil belajar siswa kelas IX SMPN 3 Dusun Selatan dalam Pendidikan Agama Kristen melalui model window shopping. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Objek tindakan yang diteliti meliputi tingkat keaktifan siswa selama mengikuti Kegiatan Belajar Mengajar dan hasil belajar siswa setelah selesai tiap siklus. Subyek siswa kelas IX SMPN 3 Dusun Selatan yang berjumlah 25 orang, terdiri dari 12 laki-laki dan 13 perempuan. Pelaksanaan penelitian pada semester 1 tahun pelajaran 2021/2022, yaitu pada bulan September sampai dengan Nopember 2021. Hasil penelitian ini menunjukkan terjadinya peningkatan yang signifikan baik pada keaktifan siswa maupun pada nilai hasil belajarnya. Peningkatan keaktifan siswa ditunjukkan dengan terjadinya peningkatan jumlah siswa yang aktif dalam proses pembelajaran pada tiap-tiap siklus. Sedang peningkatan hasil belajar siswa dibuktikan dengan terjadinya peningkatan jumlah siswa yang dapat memperoleh nilai lebih dari atau sama dengan 70 atau dapat mencapai KKM, yaitu 20 (80%) siswa pada siklus I meningkat menjadi 24 (96%) siswa pada siklus II. Dengan demikian hasil belajar siswa mencapai ketuntasan secara klasikal.